Subsoil Variability in the Bangkok Metropolitan Area of Thailand Identified through Ambient Noise Measurement - Lindung Zalbuin Mase; Weeradecth Tanapalungkorn; Panusorn Plengsiri; Kamornrat Ngamcharoen; Suched Likitlersuang (Geological Agency, 2023)
This paper presents the variations in subsoil conditions of the Bangkok Metropolitan Area of Thailand. The study was initiated by measuring ambient noise with a seismometer. A total of twenty sites was investigated by microtremor measurements. The typical subsoils of Bangkok were presented on the basis of site investigation reports. Furthermore, inversion analysis was conducted to determine subsoil properties in Bangkok. Geotechnical parameters for seismic analyses, such as soil layer thickness, undrained shear strength (su), unit weight, time-averaged shear wave velocities at 30 m (Vs30), 100 m (Vs100), and 500 m (Vs500), and engineering bedrock surface depth were reported. Results shows that clay layer thickness varies from 17 - 25 m with the su of approximately 10 - 60 kPa and unit weight of approximately 15 - 17.5 kN/m3. The results also show that Vs30, Vs100, and Vs500 fall in the ranges of 100 - 225, 175 - 300, and 325 - 450 m/s, respectively. Engineering bedrock with the Vs of 760 m/s is found at 375 - 625 m below the ground. This result also indicates that a thick sediment is generally found in the Bangkok Metropolitan Area. In general, the results of this work could be used for civil engineering practice, especially seismic design and analysis in the studied area.